David Lewin's Morgengruß text, context, commentary - Lewin, David 1933-2003 (Oxford University Press, 2015)
This title presents for the first time an extended 1974 essay by David Lewin on 'Morgengruß', a 23 measure strophic song from Schubert's 'Die Schöne Müllerin'. The essay was central to Lewin's graduate teaching, and copies of it have circulated by hand through the music-scholarly community. Yet Lewin initially wrote it for an audience of non-specialists. In addition, the book presents a preface, introduction, and three critical essays that place Lewin's work within the context of late twentieth-century music theory and the humanities - particularly phenomenology